Hubungan Pengetahuan, Sikap dan Kelelahan Kerja dengan Perilaku Safety Riding pada Pengendara Go-Jek di Kota Malang - Dwi Rahayuning Surastia; Moch. Yunus; Anita Sulistyorini; Marji Marji (Pusat Riset dan Inovasi Nasional, 2023)
East Java is a Province in Indonesia with the highest of traffic accident cases on 2022 years, it is 3.555 cases. Efforts to prevent and reduce cases of traffic accidents can be done by safety riding. The application of safety riding can be realized if it was balanced with a good knowledge and attitude by drivers on the road. Along Malang City Road are dominated by Gojek drivers with an infinite population each year. Based on preliminary studies, it was known that Gojek drivers often experience work fatigue and supported by erratic work durations even exceeded standards, which can lead to unsafe behavior when driving. The purpose of this research was to determine a relationship between knowledge, attitudes and work fatigue with safety riding behavior on Gojek drivers in Malang City. This research method used a cross sectional design with a quantitative approach and accidental sampling technique. Sample of 60 Gojek drivers in Malang City. The bivariate test used a chi square test. The results showed that there was no relationship between knowledge and attitude with safety riding behavior (p=0,697 dan p=1,000), and there was a relationship between work fatigue with safety riding behavior (p=0,000). It can be concluded that the higher level of Gojek drivers fatigue, it make more unsafe their safety riding behavior. So, it was recommended to pay more attention an enough rest time and focus while working.